Crusading and the Ottoman threat, 1453-1505 - Housley, Norman (Oxford University Press, 2013)
An assessment of the ambitious programme to refashion crusading to defend Christian Europe and to resist the advance of the Ottoman Turks into the western Balkans and central Mediterranean in the fifty years following Sultan Mehmed II's capture of Constantinople in 1453.